The effects of laser procedure in symptomatic patients with haemorrhoids: A systematic review - Torrinha, Gonçalo; Gonçalves, Tatiana; Sousa, Maria; Högemann, Gerrit; Goulart, André; Carvalho, Alexandre Fernandes; Leão, Pedro (Frontiers in Surgery, 2022)
Purpose: Haemorrhoids are normal structures in the human body, only seen as pathological when symptomatic. Nowadays, new techniques have surfaced using a diode laser which, after locating the target arteries, blocks the blood flow while hitting and shrinking the local mucosa/submucosa at a depth of 4mm. Our work aimed to give a broad view over this new technique and its consequences in the post-operative follow-up with a systematic review. Methods: EMBASE and MEDLINE databases were consulted, retrieving clinical trials, which mentioned the use of 980nm diode laser on the treatment of haemorrhoids. Results: Ten clinical trials analyzing the post-operative effects of laser haemorrhoidectomy were selected, including 2 randomized controlled clinical trials and 1 controlled clinical trial. The overall quality of the trials was low, indicating a high risk of bias. Conclusion: The laser haemorrhoidectomy procedure revealed a high therapeutic potential, considering the reduced number of postoperative complaints (bleeding/pain), the high symptom resolution and the reduced recurrence, albeit the high heterogeneity between the studies in terms of reported results. Future investigations with higher quality and controlled double-blinded studies obtaining better-categorized results should be conducted in order to better evaluate this procedure and compare it to the current paradigm. Keywords: Haemorrhoids, Diode Laser, Haemorrhoidectomy, Haemorrhoidplasty, HeLP. Funding: None. Declarations of interest: None. Consent for publication: Not applicable Availability of data and material: All materials are available for review upon request. Code availability: All employed software codes and applications are available for review upon request. Authors contributions: All authors contributed in the same manner for the following article.